2021
DOI: 10.3164/jcbn.21-10
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols reach the brain and play roles in the attenuation of body weight gain and improvement of cognitive function in high-fat diet-treated mice

Abstract: Obesity induces severe disorders such as type 2 diabetes and cardiovascular events, and the number of people with obesity is increasing all over the world. Furthermore, it is possible that obesity increases the risk of cognitive dysfunction via the acceleration of oxidative damage. Tocotrienols, which are part of the vitamin E family, have antioxidant and anti-obesity effects. However, the effects of tocotrienols on high-fat diet-treated mice have not been completely elucidated. In this study, we assessed chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…The fall time in the rota-rod test tends to be body-weight-dependent. In our previous study, obese mice fell faster than age-matched controls, and a negative correlation between body weight and fall time was observed [ 28 ]. In this study, the mean body weights of the AD mice at each age were lower than those of the age-matched controls, despite being fed ad libitum (control 3-month-old (3 M), 22.44 g; control 6-month-old (6 M), 30.8 g; Control 20-month-old (20 M), 29.18 g; AD 3 M, 18.6 g; AD 6 M, 20.4 g; AD 20 M, 24.2 g).…”
Section: Discussionmentioning
confidence: 99%
“…The fall time in the rota-rod test tends to be body-weight-dependent. In our previous study, obese mice fell faster than age-matched controls, and a negative correlation between body weight and fall time was observed [ 28 ]. In this study, the mean body weights of the AD mice at each age were lower than those of the age-matched controls, despite being fed ad libitum (control 3-month-old (3 M), 22.44 g; control 6-month-old (6 M), 30.8 g; Control 20-month-old (20 M), 29.18 g; AD 3 M, 18.6 g; AD 6 M, 20.4 g; AD 20 M, 24.2 g).…”
Section: Discussionmentioning
confidence: 99%
“…As obesity raises the risk of several diseases, such as type-2 diabetes, cardiovascular disease, and atherosclerosis, the prevention of obesity is very important [ 21 , 22 , 23 ]. It has been reported that T3s have an anti-obesity effect in HFD-treated mice [ 9 , 10 , 11 ]. However, the underlying mechanism of this effect has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that T3s inhibit HFD-induced hepatic lipid droplet accumulation [ 11 ]. To reveal the effects of T3s on serum lipid metabolism, cholesterol concentrations in serum were measured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations